Enhancing Infusion Pump Calibration through Evaluating Occlusion Sensor Performance in a Dual-Channel Infusion Device Analyzer - Asrori’, Ach Jiddan; Yulianto, Endro; Rahmawati, Triana (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Occlusions frequently hinder the continuous delivery of medications or fluids through syringes and infusion pumps, posing a critical challenge in medical practice. To address this issue, the infusion set occlusion threshold has been established at 20 Psi, guided by ECRI standards. Annual recalibration is essential to ensure compliance with this benchmark. This study focuses on appraising the precision of a pressure sensor integrated into a dual-channel TFT display infusion device analyzer. The innovative dual-channel design streamlines the concurrent calibration of two medical instruments, enhancing efficiency. The research employs a water pressure sensor to detect occlusions and a solenoid valve to simulate pressure conditions. Upon pressure detection, the sensor transmits data to an Arduino for processing. Results are vividly displayed on a 7-inch TFT LCD screen, providing real-time graphical and numerical insights, which are also stored on an SD card. Significant findings reveal distinct error margins across devices: 2.84% for the Terumo TE-331 Infusion Pump, 7.26% for the TOP-5300 Infusion Pump, a notable 58.20% for the TOP-3300 Infusion Pump, and a striking 71.26% for the Infusia VP7 infusion, indicative of pressure accuracy variations. Notably, the SEN0257 sensor exhibits superior precision when integrated with a syringe pump, showcasing a more favorable error rate compared to larger infusion pumps. This study's implications extend to the critical domain of infusion pump calibration, offering a valuable reference for assessing device suitability. The research contributes not only to refining infusion accuracy but also offers a practical framework for optimizing medical device performance, thus enhancing the overall quality of patient care.